2016
DOI: 10.1590/0001-3765201620150140
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of hepatitis B virus in the cities of the northern region of Espírito Santo, Brazil

Abstract: The World Health Organization (WHO) estimates that approximately 2 billion people worldwide have already had contact with hepatitis B virus (HBV) and 373 million have become chronic carriers. Hepatitis B is a major cause of chronic hepatitis, cirrhosis and hepatocellular carcinoma, leading to a large number of deaths annually. Both viral factors and the host immune response have been implicated in the pathogenesis and clinical result of HBV infection. Many Brazilian cities, including the cities of the northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
0
1
0
2
Order By: Relevance
“…O oposto frente ao sexo foi identificado no Espírito Santo, com predomínio de casos femininos e idades entre 20 a 49 anos. Fato possivelmente explicado devido a tendência de as mulheres recorrerem mais aos serviços de saúde (11) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…O oposto frente ao sexo foi identificado no Espírito Santo, com predomínio de casos femininos e idades entre 20 a 49 anos. Fato possivelmente explicado devido a tendência de as mulheres recorrerem mais aos serviços de saúde (11) .…”
Section: Resultsunclassified
“…Além do uso de drogas injetáveis, do tratamento odontológico e contágio via sexual com indicação de múltiplos parceiros, o contato domiciliar com outra pessoa infectada pelo HBV também foi destacado (11) . A coinfecção com o HIV entre os casos notificados de hepatite B foi observada em 5,2% dos casos acumulados no período de 2007 a 2017, com elevação para a região Sudeste do Brasil, o que reitera a importância do diagnóstico, facilitado gratuitamente por meio dos testes rápidos (3) .…”
Section: Resultsunclassified
“…Multiple regression analysis, as well as the other studies, revealed an association between exposure to HBV and age increase [14, 20, 36, 40]. The displacement of the epidemiological curve of HBV in populations with higher age groups can be explained by the Brazilian policy of increasing the age for eligibility of hepatitis B vaccine over the years [34].…”
Section: Discussionmentioning
confidence: 96%